Increased HIF-1alpha And VEGF Expression Found in Various T Stages of Clear Cell Renal Cell Carcinoma - Octavianda, Yohana; Rahaju, Anny Setijo (Folia Medica Indonesiana, 2018)
There is an increase in renal cell carcinoma in males aged over fifty years with smoking risk factors. Clear cell renal cell carcinoma is the most common malignant tumor found in the kidneys that have an aggressive nature. This carcinoma is classified according to TNM into T1, T2, T3 and T4 stages. The higher the T stage, the worse the prognosis of the patient, as it involves the role of the HIF-1a transcription factor accumulated under hypoxic condition due to inactivation of VHL, thus activating VEGF. So far, clear cell renal cell carcinoma frequently found in smoking males of fifth decade of age or older has not been explained.. An observational analytic study was conducted on the sample of paraffin blocks of patients with clear cell renal cell carcinoma in 2010-2016. T1, T2, T3, and T4 stages of 9 samples, 12 samples, 12 samples and 6 samples, respectively, were collected in Anatomic Pathology Laboratory, Dr. Soetomo Hospital, Surabaya. Detection of HIF-1a and VEGF expression was performed using immunohisto-chemical immunity with HIF-1a and VEGF antibodies. The results were analyzed statistically by Kruskal-Wallis and Mann-Whitney methods. The correlation between HIF-1a and VEGF in T stages was analyzed using Spearman method. There was a difference of HIF-1a expression between stage T1 with T2, T1 with T3, T1 with T4 (p=0.041, p=0.000, and p=0.002), stage T2 with T3 and stage T2 with T4 (p=0.001, and p=0.013). There was a difference in VEGF expression in stage T1 with T2, T1 with T3, T1 with T4 (p=0.007, p=0.000, and p=0.002), and stage T2 with T3 (p=0,001). There was a correlation between HIF-1a and VEGF expressions with all T stages (rs=0.624 with p 0.000). As a conclusion, the higher the stage of T, the higher the expression of HIF-1a and VEGF. The higher the levels of HIF-1a and VEGF, the worse the prognosis of clear cell renal carcinoma. HIF-1a and VEGF play a role in the pathogenesis of clear cell renal cell carcinoma. Thus, HIF-1a and VEGF can be developed as prognostic markers. Increased Hif-1aAnd Vegf Expression Found In Various T Stages Of Clear Cell Renal Cell Carcinoma